A flow cytometric assay for the quantification of MSC lysis by peripheral blood mononucleated cells. Issue 2 (February 2021) - Chieregato, Katia; Bernardi, Martina; Alghisi, Alberta; Giordano, Rosaria; Lazzari, Lorenza; Perbellini, Omar; Rassu, Mario; Ruggeri, Marco; Astori, Giuseppe
Abstract: Mesenchymal stromal cells (MSC) are attractive candidates for the treatment of acute graft versus host disease (aGvHD) or autoimmune disorders. However, mechanisms of MSC recognition remain unclear and there are evidences that MSC are not totally immunoprivileged. Data suggest that MSC undergo apoptosis after infusion in presence of cytotoxic cells and their death could drive immunosuppression. In GvHD patients, that activity was associated with clinical response. It is mandatory to develop an in vitro potency testing predictor of the "in vivo" response to the therapy. We describe a flow cytometric assay based on differential immunostaining of target and effector cells where BM MSC are enumerated with fluorospheres to determine the loss of target cells after co-culture with PB MNC. 6/13 (46%) of BM MSC lots were lysed by PB MNC and the lysis was proportional to the E/T cell ratio. The method overcomes the problems linked to the use of dyes or radioactive, evidencing the limitations linked to the use of a single vital dye and proposing a precise gating strategy based on absolute cell counts where cells are left untouched. The assay is easy and could be used to predict the response of the patients to the therapy. Abstract : Mesenchymal stromal cell; Absolute count; Cytotoxicity; Graft versus host disease; Apoptosis